High-grade atrioventricular block occurring during percutaneous closure of patent foramen ovale: a case report. Issue 4 (25th June 2020) - Kibler, Marion; Marzak, Halim; Jesel, Laurence; Ohlmann, Patrick
Abstract: Background : Percutaneous closure of patent foramen ovale (PFO) is recommended for patients presenting with PFO-related stroke. Acute high-grade conduction disturbances occurring during PFO closure procedure have not been previously reported. Case summary : We describe for the first time a case of reversible complete atrioventricular block which occurred during closure of a PFO. Discussion : We hypothesized that the block was the result of atrioventricular node compression—likely caused by the right-atrial disc of the 35-mm PFO closure device. We suggest implanting smaller devices in order to prevent atrioventricular conduction disturbances.